Analisis Dampak Pemekaran Wilayah Terhadap Pendidikan di Kecamatan Bulik Timur Kabupaten Lamandau Kalimantan Tengah - Delviani, Fristhy; ., Fitriyah; Astrika, Lusia (Journal of Politic and Government Studies, 2015)
According to law no 32 of 2004 article 4 paragraph 3 , the formation of a territory can be done by the merger of two regions that bersandingan or may be done by means of the segregation of .Including kecamatan bulik the east who also is the result of a part of the kecamatan bulik .It is hoped that the region between will be able to close and improve the service for people , so can not use public services not only warg in the city center but to also to the residents of the outskirts .Especially is education , where education is one of the basic rights of which may be obtained citizen without discrimination .This research take focus on the impact of the region against the segregation of education in east sub-district bulik.So as to get a description for, writer using qualitative methodology type descriptive.In this research , seen that the segregation of after it has occurred have been built a lot of infrastructure education , among them are the addition of four units of new junior high school , three pieces of high school or the equivalent level , 3 units of primary school , and some a preschool education .Besides that also have been built land infrastructure that is easy to reach out to the school students whether it is with a motor , ride a bike , or on foot .Unfortunately , there has been no mass transportation that are amenable to access the school students .Efforts need to be done more serious by the district government lamandau to help children who have access difficult against the school, as for example transport menyediaakan school provision of transportation facilities mass and infrastructure improvement army.Besides, also need to be done the recruitment efforts of teachers continuously educator so that the quality of this region not lose compete with educator from other .